How is Student Resilience in Academic Activities? Measurement in Indonesia - Herul Wahyudin; M. Ramli; Maria Oktasari (Proceedings Series of Educational Studies, 2023)
This paper explores the significance of gauging academic resilience in students, which is crucial for their academic success and overall well-being. Academic resilience is defined as a student's capacity to overcome educational challenges and hurdles. The paper underscores the necessity of assessing academic resilience to pinpoint students who may require intervention and assistance. It also delves into the four facets of academic resilience: confidence, control, composure, and persistence. The research, conducted in Indonesia with 599 middle school students, utilized a self-constructed scale to measure academic resilience. The findings revealed a moderately average level of academic resilience among the students. The paper stresses the need to boost students' confidence, control, composure, and persistence to augment their academic resilience. The research also scrutinized the academic resilience of students based on demographic factors such as gender, grade level, and province. The findings indicated significant resilience differences based on gender and province. The study further investigated the resilience variation based on specific items of the academic resilience scale. Several items exhibited differential functioning based on demographic factors.